A kingdom united: British and Irish popular responses to the outbreak of war, July to December 1914 - Pennell, Catriona (Trinity College (Dublin, Ireland). Department of History, 2008)
In the current literature on Britain and Ireland during the First World War there is a significant gap concerning public responses to the outbreak throughout the autumn of 1914. My project rectifies this situation by being the first systematic analysis of British and Irish public opinion at the outbreak of the Great War. The first aim of the thesis is to replace simplistic accounts of war enthusiasm by a more nuanced and complex picture of popular sentiment in Britain and Ireland. The second is to integrate Ireland into a UK-wide study of the First World War. This thesis takes a chronological, analytical and thematic approach to the outbreak of war in 1914. Chapter One details feelings of tension in the lead-up to the announcement of war on 4th August and follows the chaos and disruption that followed during the first few weeks of the conflict. Chapters Two to Four examine three dominant themes in detail- the national cause, perceptions of the enemy, and encounters with violence, both real and imagined. Chapter Five looks closely at the importance of volunteerism in the British experience of ‘entering’ war, and, in particular, questions whether enlistment to the army was indicative of enthusiasm for war. Although Wales and Scotland are integrated into the thematic, regional and chronological analysis of the previous chapters, Chapter Six is dedicated solely to Ireland owing to the uniqueness of her political situation in 1914. Ireland was both divided internally over Home Rule and at odds with Britain. How united was the United Kingdom following the outbreak of war? Chapter Seven looks at the United Kingdom as a whole between September and December 1914 establishing to what extent British and irish people ‘settled’ into war. Going ‘below’ generalised national histories, my project places equal weight on ‘national’ and regional reactions to the outbreak of war. I have constructed the national picture using such sources as The Times and other major national newspapers, memoirs and papers of contemporary political figures, parliamentary debates and external eyewitnesses such as foreign diplomats. This research allowed me to build up an impression of responses, such as anti-German riots, fears of invasion, popular myths about the war, food hoarding, alien arrests, patriotic demonstrations and dissent. However, the national perspective has not subsumed local reactions. Comparison means selection, and I have therefore chosen a variety of regions to study, based on geographical position, demography and comparative potential. My comparison encompasses not just parts of England but also Scotland, Wales and Ireland (north and south) so that I am able to draw conclusions at the level of the United Kingdom as a whole. Within England I have chosen to compare Essex, Devon, Lancashire, London and the West Midlands. Essex was selected for investigation as it was on the ‘front’ of the British home front in 1914 and was compared with Devon, another rural county. Lancashire and the West Midlands were selected as major urban industrial centres of the United Kingdom in 1914. London, as capital, was selected in order to provide a sense of reactions to the war at a ‘national’ level. I approached each ‘zone’ in a similar way. The thematic grid that I established at the national level was placed over local sources, such as diaries, letters, committee minutes, cartoons, photographs, oral recollections, memoirs and newspapers. This allowed me to compare national and regional reactions and also to compare different regional reactions. This thesis makes two fundamental conclusions. Firstly, it demonstrates that describing the reactions of over 40 million British and Irish people to the outbreak of war in 1914 as either enthusiastic in the British case or disengaged in the Irish is over-simplified and inadequate. A society as complex as the United Kingdom in the Edwardian era did not have a single, uniform reaction to such a major event as the outbreak of European war. Emotional reactions to the war were ambiguous and complex, and changed over time. A general emotional chronology can be traced over the course of the first five months of war. Surprise at the outbreak of war on 4th August was followed by a fortnight of chaos and dislocation. However, by late August the majority of the population were beginning to understand what was involved in modern warfare. People voluntarily rallied around the national cause, purged their fears of the external German enemy by seeking scapegoats within, in the form of enemy spies and aliens, and imagined and encountered violence. By early-September most people were firmly ‘inside the war’, of which they could see no end. The second conclusion derives from situating Ireland firmly within the history of the United Kingdom at war in 1914. Whilst domestic politics in Britain were suspended, just as in France and Germany, war became part of the politics of domestic peace in Ireland. Despite concerns over potential dissidence amongst Irish nationalists, following the outbreak of war the majority of Irish men and women of all political persuasions rallied around the British cause and supported the war. Any dissent amongst advanced nationalists was limited and those involved knew how constrained their position was. Therefore despite the fragility of the relationship between Britain and Ireland, Kingdom was United in 1914.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin